(untitled) (Kinesiology, 2019)
The aim of the study was to compare the effects of an in-season 5-week high-intensity training (HIT) with a concurrent HIT plus eccentric overload training (CT) program on male amateur team-sports players’ fitness performance. Twenty-two athletes were randomly assigned to HIT (n=10) or CT (n=12). Both groups completed a HIT program. The CT group also completed 2-3 sets × 6 repetitions of eccentric overload training. Before and after training, performance was assessed for flexibility, change of direction ability (COD), repeated sprint ability for best time (RSAb), mean time (RSAm) and slowest time (RSAs), jumping, endurance, and VO2max. Within-group analyses in both groups showed substantial better scores on RSAb and RSAm, COD, endurance and VO2max. Between-group analyses showed greater improvements in RSAb, RSAs, RSAm, COD, and jumping after CT compared to HIT. In conclusion, compared to HIT alone, concurrent eccentric overload and HIT training within the same session concurrently improved RSA, COD, jump, and endurance performance.